Meniscus-Related Videos on TikTok Are Widely Viewed and Shared but the Educational Quality for Patients Is Poor - Riccardo D'Ambrosi, M.D; Timothy E. Hewett, M.D (Elsevier, 2024)
Purpose: To evaluate the quality of meniscus-related TikTok videos to better understand their value for patient education. Methods: The term "meniscus" was used as the key word for an extensive online search of video content on the TikTok on November 14, 2023. The first 100 videos were used for analysis. The duration of the videos and the number of likes, shares, and views were recorded for each video. Furthermore, videos were categorized based on the source (health workers, private user), the type of subject (patient experience, physical therapy, anatomy, clinical examination, surgical technique and injury mechanism), type of content (patient experience/testimony, education, rehabilitation), and the presence of music or voice. The quality and reliability assessments of video contents were conducted using the DISCERN instrument, the Journal of the American Medical Association benchmark criteria, and Global Quality Score. Results: Of the 100 videos included in this study, 62 (62%) videos were published by health workers and 38 by private users (38%). Most of the information regarded patient experience (36, 36%), followed by physical therapy (32, 32%), anatomy (14, 14%), clinical examination (8, 8%), surgical technique (6, 6%), and injury mechanism (4, 4%). Video content reported patient experience in 39 (39%) videos, rehabilitation in 31 (31%) videos, and education in the remaining 30 (30%). The mean length of the videos was 39.12 ± 49.56 seconds. The mean number of views was 1,383,001.65 ± 5,291,822.28, whereas the mean numbers of comments, likes and shares were 408.53 ± 1976.90, 54,763.43 ± 211,823.44 and 873.70 ± 2,802.01, respectively. The mean DISCERN score, Journal of the American Medical Association benchmark criteria score, and Global Quality Score were 17.93 ± 5.07, 0.24 ± 0.47, and 1.15 ± 0.41, respectively. Conclusions: Meniscus-related videos on TikTok are widely viewed and shared but the overall educational value to patients is poor. Clinical Relevance: As patients increasingly use social media to learn about their conditions, it is important for orthopaedic health care professionals to understand the limitations of TikTok videos addressing the meniscus as potential sources of information for their patients.